2009
DOI: 10.3147/jsfp.44.40
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Drug Resistance in Streptococcus parauberis Isolated from Japanese Flounder

Abstract: ABSTRACT-Antimicrobial susceptibility of Streptococcus parauberis against nine drugs were investigated in 64 strains isolated from Japanese flounder Paralichthys olivaceus at different culture areas of western Japan, and resistance genes were determined by PCR and Southern blot hybridization. Five of the tested strains belonging to S. parauberis serotype I (44 strains) were resistant to oxytetracycline and erythromycin and were found to possess both tet (S) and erm (B) genes. Minimum inhibitory concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…The results obtained in this study are consistent with those of previous reports indicating that ERY and OTC have limited efficacy toward S. parauberis isolated from olive flounder (Jeong et al, 2006;Park et al, 2009). Meng et al (2009) reported that S. parauberis strains with high-level resistance to OTC are often associated with resistance to ERY. This is likely because most erm genes encoding ERY resistance proteins are carried on transposons, and through transposition become linked to tet genes encoding tetracycline or OTC resistance proteins.…”
Section: Antibiotic Resistance Of Streptococcus Parauberis Strainssupporting
confidence: 93%
“…The results obtained in this study are consistent with those of previous reports indicating that ERY and OTC have limited efficacy toward S. parauberis isolated from olive flounder (Jeong et al, 2006;Park et al, 2009). Meng et al (2009) reported that S. parauberis strains with high-level resistance to OTC are often associated with resistance to ERY. This is likely because most erm genes encoding ERY resistance proteins are carried on transposons, and through transposition become linked to tet genes encoding tetracycline or OTC resistance proteins.…”
Section: Antibiotic Resistance Of Streptococcus Parauberis Strainssupporting
confidence: 93%
“…According to our findings it is likely that the prevalence of the tet (M)‐positive serotype II strains in Japan are due to clonal dissemination of a original strain that acquired the Tn 916 ‐like element from another bacterial species rather than selection of tet (M)‐positive strains by frequent use of tetracyclines. This hypothesis is supported by the fact that all of the tested serotype II strains were also low resistant to erythromycin (Meng et al. 2009).…”
Section: Discussionmentioning
confidence: 79%
“…However, the worldwide use of tetracyclines for the control of infections, as prophylactic agents or as growth promoters, has facilitated the emergence and spread of acquired resistance (Roberts 2005). In our preliminary experiments (Meng et al. 2009), tetracycline‐resistant strains of S. parauberis serotype I and II were found in our culture collections, and, surprisingly, all of serotype II strains derived from divergent aquaculture sites were tetracycline‐resistant and harboured tet (M), xis (excisase) and int (integrase) genes which are components of Tn 916 family transposons (Clewell et al.…”
Section: Introductionmentioning
confidence: 90%
“…Strains of Streptococcus parauberis have previously shown resistance against different antimicrobial drugs such as tetracycline, oxytetracycline, and erythromycin [43,44]. Because of the chance of antibiotic resistance, there is a need for new and alternative therapeutic targets against this pathogenic bacterium.…”
Section: Discussionmentioning
confidence: 99%